1983
DOI: 10.1177/030098588302000211
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Volume Distribution Analysis and Hematologic Changes in Dogs with Iron Deficiency Anemia

Abstract: Abstract. Hematologic features were characterized in 12 dogs with iron deficiency anemia attributable to chronic external blood loss. Consistent abnormalities in hemograms included moderate to marked reticulocytosis, decreased mean corpuscular volume, and decreased mean corpuscular hemoglobin concentration. Hypoproteinemia occurred in only four of 12 dogs. Consistent blood film findings included hypochromic cel1s, leptocytosis, and erythrocyte fragmentation. These dogs had significantly decreased serum iron va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 19 publications
(16 reference statements)
3
26
1
Order By: Relevance
“…However, leptocytes, or tagetshaped cells, in mammals seem to be similar to the deformed erythrocytes; leptocytes have relatively low cellular material compared to their cell surfaces. There is a report demonstrating that leptocytosis in dogs was induced by iron deficiency anemia attributable to chronic external blood loss (Weiser and O'Grady, 1983). The erythrocytes in the bled and unfed fish in the present study often showed an insufficient accumulation of Hb.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…However, leptocytes, or tagetshaped cells, in mammals seem to be similar to the deformed erythrocytes; leptocytes have relatively low cellular material compared to their cell surfaces. There is a report demonstrating that leptocytosis in dogs was induced by iron deficiency anemia attributable to chronic external blood loss (Weiser and O'Grady, 1983). The erythrocytes in the bled and unfed fish in the present study often showed an insufficient accumulation of Hb.…”
Section: Discussionsupporting
confidence: 46%
“…In recent years, anemia has been prevailing in both wild and cultured Japanese flounder, Paralichthys olivaceus, in Japan (Miwa and Inouye, 1999;Yoshinaga et al, 2000;Mushiake et al, 2001). The anemia is hematologically characterized by the appearance of immature erythrocytes, deformed erythro cytes and abnormal erythrocytes having weakly stained or vacuolated cytoplasm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…47,48 Since iron is preferentially used for hemo- however, a few weeks of iron deficiency are still needed before abnormalities are detected. 56 In contrast, the CHr decreases within a few days of iron-deficient erythropoiesis.…”
Section: Reticulocyte Indicesmentioning
confidence: 99%
“…The concentration of the iron standard minus the unbound iron is called the unbound iron-binding capacity (UIBC), which is used to calculate the TIBC (UIBC plus total serum iron concentration). TIBC is increased in iron deficiency in humans, horses, cattle, and pigs, but does not appear to be increased in clinical iron deficiency in dogs [2,3] . In a study by [4] , TIBC levels in sheep exposed to dietary limitation were higher than that of control group.…”
Section: Introductionmentioning
confidence: 99%